A corneal dermoid in a black wildebeest Connochaetes gnou - A. Weber; W. van Hoven (Koedoe: African Protected Area Conservation and Science, 1990)
Dermoids are choristomatous malformations that can occur in the ocular region with a histologic structure similar to that of normal skin. Dermoids occur in a variety of domestic animals but no such cases have been reported in wild animals. A typical corneal dermoid in a black wildebeest Connochaetes gnou is presented.